Determination Of Permissible Level Of Aflatoxin In Broiler Chicken Feed - Arulmozhi A (Department of Pathology, College of Veterinary and Animal Sciences, 1999)
The study was undertaken to assess the effect of various levels of aflatoxin on the performance of broilers and to establish the permissible level of aflatoxin in the broiler feed. One hundred and eighty day old broiler chicks were divided into six groups of 30 birds each and were given feed containing graded levels of aflatoxin at 0, 20, 40, 60, 80 and 100 ppb for a period of 45 days. Feed intake, weekly body weight gain, feed efficiency, haemogram, serum profile, organ weight, residual aflatoxin in tissues and pathological changes in liver, kidney, bursa and spleen were studied at fortnightly intervals to evaluate its dose related effects. A dose dependent decrease in the daily feed intake and mean body weights were noticed in all the groups. The cumulative FeR was extremely poor at 80 and 100 ppb levels at sixth week of age. The toxicopathological changes in the birds varied in its intensity in relation with the level of aflatoxin in the feed, with most severe changes being at higher dose levels. The values of haemoglobin, PCV, total leucocyte count, Iymphocytes, total serum protein and albumin showed a decrease whereas the ESR, heterophil and serum enzyme were increased.